Effect of soot on tribological properties of steel and ceramic contacts. (27th June 2019) - Kaushik, Yadvendra; Ramkumar, P.
The present study aims to understand the effect of soot on tribological properties using different tribo-couples of bearing steel, silicon nitride and zirconia. The present test programme is performed using a pin-on-disc tribometer with LVDT, temperature and friction transducers. All tests are carried out at a sliding speed of 5 m/s and contact stress of 2.05 GPa to simulate a typical valve-train operation condition in diesel engine. Commercially available heavy-duty diesel engine oil is used as lubricating oil. Friction and wear results are studied at different levels of soot concentration. Silicon nitride shows the lowest friction and wear against the bearing steel amongst the all tribo-couples. Post-test analysis is carried out using optical microscope and SEM with EDX of the worn surfaces of the pin materials to identify the wear mechanisms. Abrasive wear mechanism was found to be the primary wear mechanism for all tribo-couples. A delamination wear mechanism is proposed for zirconia in presence of soot contamination.